2021
DOI: 10.1111/jfbc.13909
|View full text |Cite
|
Sign up to set email alerts
|

Polygonum odoratum leaf extract attenuates oxidative stress and cell death of Raw 264.7 cells exposed to low dose ionizing radiation

Abstract: This study aims to investigate the effect of Polygonum odoratum leaf extract (POE) on oxidative stress markers and cell death induced by low dose ionizing radiation (LDIR) in Raw 264.7 cells. The biological activities, chromatographic fingerprint, and cytotoxicity of POE were investigated. To determine the radioprotective effect of POE, Raw 264.7 cells were incubated with POE for 1 hr prior to 100 mGy x-irradiation.The cell viability, oxidative stress damage marker (malondialdehyde level; MDA), and endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In contrast, the compound or the free aglycone moiety was not detected in the leaf extract of P. odoratum in studies by Pawłowska et al (2020) and Ahongshangbam et al (2014) , and only a small amount was detected in a study by Kawvised et al (2021) . Gallic acid was the predominant constituent in aqueous leaf extract ( Kawvised et al, 2021 ).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In contrast, the compound or the free aglycone moiety was not detected in the leaf extract of P. odoratum in studies by Pawłowska et al (2020) and Ahongshangbam et al (2014) , and only a small amount was detected in a study by Kawvised et al (2021) . Gallic acid was the predominant constituent in aqueous leaf extract ( Kawvised et al, 2021 ).…”
Section: Resultsmentioning
confidence: 87%
“…In contrast, the compound or the free aglycone moiety was not detected in the leaf extract of P. odoratum in studies by Pawłowska et al (2020) and Ahongshangbam et al (2014) , and only a small amount was detected in a study by Kawvised et al (2021) . Gallic acid was the predominant constituent in aqueous leaf extract ( Kawvised et al, 2021 ). Tannins were not detected in a screening test by Devi Khwairakpam et al; in contrast, another study reported a high abundance of this class of compounds ( Kumar and Chaiyasut, 2017 ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast, secretion of IL-6, but not TNF-α, was found to be significantly reduced in a concentration-dependent manner with 50% and 100% ethanolic extracts (10-100 µg/mL) of P. odoratum leaves (IC 50 = 25 µg/mL), the scutellarein-7-glucoside fraction (IC 50 = 102 µM) and the quercitrin (IC 50 = 77 µM) extract, all of which emphasized the anti-inflammatory activity of scutellarein-7-glucoside and quercitrin [15]. Moreover, the hot water extract of P. odoratum leaves, which are known to be abundant with TPC (223.0 ± 9.7 mg GAE/mg extract) and comprise GA (7.63 ± 0.30 mg/g), ellagic acid (3.31 ± 0.14 mg/g), C (1.77 ± 0.10 mg/g), rutin (0.40 ± 0.20 mg/g), Q (0.08 ± 0.01 mg/g), caffeic acid (0.07 ± 0.01 mg/g), kaemferol (0.02 ± 0.00 mg/g) and ferulic acid (0.02 ± 0.00 mg/g), exerted antioxidant activities by decreasing malondialdehyde levels while increasing levels of catalase, superoxide dismutase and glutathione peroxidase activities in RAW264.7 cells exposed to X-ray irradiation [35]. Furthermore, the water extract of P. odoratum leaves decreased contractions of 80 mM potassium chloride-induced rat ileum in a dose-dependent manner, possibly by increasing the production of NO • via the β-adrenergic receptor pathway and by blocking the calcium influx [36].…”
Section: Discussionmentioning
confidence: 97%